Analisis Pengembangan Buku Saku Pendidikan Seks di TK Kartika Kota Pontianak - Risa Rusmaniah; Diana Diana; Yuniarti Yuniarti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The increasing cases of sexual violence in early childhood make it important to provide education about early childhood sex education, so that children can protect themselves from acts of sexual violence. The purpose of the study was to analyze a sex education pocket book for children aged 5-6 years at Kartika Kindergarten, Pontianak City. The research method uses research and development with a 3-D development model (Define, Design, Develop). The define stage includes analyzing students and concepts. The design stage includes designing media and materials. The develop stage includes expert validation. The pocket book material includes introduction to the body and limits of aurat, body parts that can and should not be touched, how to refuse inappropriate touch, and sexual violence complaint centers. The results showed that the pocket book “Ku Jaga Diriku” contains material on body recognition, aurat boundaries, touching that is allowed and prohibited, and how to protect yourself, material and media expert validation showed that the pocket book was very valid with a score of 100%, small and large scale trials showed that children's responses were very appropriate with a score of 100%, the pocket book effectively increased children's understanding of sex education.